Pelatihan Pembuatan Hand Sanitizer Berbahan Lokal dalam Upaya Pemberdayaan Kesehatan Masyarakat Desa Karang Dima Kabupaten Sumbawa di Masa Pandemi Covid-19 - Nurhidayati, Siti; Khaeruman, Khaeruman; Anggraeni, Ni Kadek Dwityasari (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2022)
Hand sanitizers are a community need during the Covid-19 pandemic. The availability of hand sanitizers is very small, so they are sold at relatively expensive prices on the market. One solution to the need for public health during the Covid-19 pandemic is to use hand sanitizers made from local materials that can be found in the surrounding environment. However, public knowledge about this is very low. For this reason, this service is carried out to provide knowledge and skills to the community on how to make hand sanitizers made from local materials that are environmentally friendly and economical, such as: betel leaf and lime. This service activity is carried out in 4 (four) stages, namely: 1) interviews and observations, to find out the initial conditions of the people of Karang Dima Village, Sumbawa Regency and local materials that can be used for making hand sanitizers; 2) socialization to the community about the importance of maintaining cleanliness; 3) training and hands-on practice of making hand sanitizers made from local ingredients and their packaging; and 4) assistance. The enthusiasm of the community during the training was very high, and the result of the training was that the community had qualified skills in making their own hand sanitizer, which was much needed.